Being “hangry”: gastrointestinal health and emotional well-being in the long nineteenth century - Taylor-Brown, E (Springer, 2018)
This essay explores the tropes and metaphors that make up the nineteenth-century literary and scientific aesthetics of gastrointestinal health, paying attention to the ways in which these frameworks blurred the boundaries between analogy and lived experience. This was a time apparently beset by the emotional violence of improper digestion, speaking to the recent term “hangry” to mean “being angry as a result of being hungry”, which too forwards a physiologically embodied understanding of anger. In the nineteenth century, this phenomenon intervened in debates concerning the interconnectedness of the gastrointestinal and psychiatric or neurological systems. From chronic indigestion to dyspeptic hypochondriasis, the lexis of violence was one of the many lenses through which writers strove to pin down the mechanics of digestive health.